Cognition across the psychiatric disorder spectrum: From mental health to clinical diagnosis - Susan L. Rossell (Frontiers Research Topics, 2015)
Psychiatric symptoms are considered to be distributed along a continuum, from good mental health to a diagnosable psychiatric disorder. In the case of psychosis, subclinical psychotic experiences, which can include odd behaviors, strange speech, unusual perceptual experiences and social/emotional withdrawal, are often referred to as schizotypy. Research examining schizotypal traits in non-clinical populations is rapidly expanding. The exploration of schizotypy allows us to identify areas of overlap with psychiatric disorders (schizophrenia and related disorders) at genetic, biological, environmental and psychosocial levels, thus identifying putative risk factors, as well as exploring potentially protective factors. Schizotypy is also a valuable model for exploring cognition as performance is not confounded by issues often present in schizophrenia samples, such as long-term antipsychotic medication usage, social isolation, and recurrent hospitalizations. Investigating cognition is a particularly important area of research as cognitive symptoms in schizophrenia, such as impaired attention, reduced memory and difficulties with executive functions, are a core feature of schizophrenia and strongly related to quality of life and functional outcomes, yet generally respond poorly to current treatment options. The aim of this special Research Topic is to explore the relationship between cognition, schizotypy and the schizophrenia spectrum. The articles in this e-book draw on a variety of perspectives and represent an interesting array of opinions, reviews and empirical studies that begin to answer questions about the similarities and overlaps between schizotypy and schizophrenia spectrum disorders, contributing to our understanding of potential risk factors. Equally important is research that highlights differences between schizotypy and schizophrenia spectrum disorders that may enhance our understanding of potentially protective or adaptive features of schizotypy. Collectively, these articles highlight the exploratory potential of the study of schizotypy, particularly in relation to better understanding cognition across the schizophrenia spectrum.